Check Out or Call Out: Attitude-Driven Boycott Intention in The Fashion Industry - Balatbat, Maricel S.; Ang, Andrea Jean C.; Castillo, Kharylle Camilla O.; Nañoz, John Emmanuel R.; Blasa-Cheng, Angelique C.; Vergara, Raymond Allan G.; Vergara, Kimberly Christie S. (Future Science / FSH-PH Publications, 2023)
Purpose – This paper aims to contribute to the study of the factors of consumers’ attitudes toward boycott intention. This examines how behavioral beliefs and attitudes are statistically related to boycott intention through the modified conceptual framework of Ajzen’s Theories of Reasoned Action and Planned Behavior. Design/methodology/approach – Human behavior concerning boycott intentions is studied using a sequential explanatory research design. Data are obtained from 90 valid respondents through questionnaires and 8 interviewees from focus group discussions. It was analyzed using regression analysis and Baheiraei's points of integration. Findings – Animosity, legitimacy, and boycott attitude significantly affect boycott intention. Boycott attitude served as a mediator between legitimacy and boycott intention. Weak evidence shows that ethical relativism and animosity significantly affect boycott attitudes. Research Limitations/Implications – The study is limited to millennials and Generation Z Filipino fashion consumers who have substantial purchasing power and awareness of social events. Practical/Social Implications – This paper shall help companies and researchers better understand the motives behind boycott intentions for ethical decision-making processes and further engage in social and moral involvements within the community. Originality/value – The study proposes the addition of relevant variables to studies on boycott intention in the fashion industry. This may help increase the understanding of consumer attitudes leading to boycotts and aid a company in countering boycotts.